Умка хочет летать: сказки / М. Пляцковский - Пляцковский Михаил Спартакович (Планета детства, 2006)
Экземпляры: ф. 3 (20081120) / Инвентарный номер: 92806 / Цена: 83.27 / Авт.знак: П 40 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6